2021
DOI: 10.1021/acs.est.0c08631
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Methanogens in Microbial Reductive Dechlorination of Organic Chlorinated Pollutants In Situ

Abstract: Previous studies often attribute microbial reductive dechlorination to organohalide-respiring bacteria (OHRB) or cometabolic dechlorination bacteria (CORB). Even though methanogenesis frequently occurs during dechlorination of organic chlorinated pollutants (OCPs) in situ, the underestimated effect of methanogens and their interactions with dechlorinators remains unknown. We investigated the association between dechlorination and methanogenesis, as well as the performance of methanogens involved in reductive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Our previous studies found that PCB71 and PCB149 could be extensively dechlorinated in Hudson and Grasse River sediments with similar levels of Dehalococcoides but with a more prevalent methane production. , It was reported that methanogens might assist dechlorination through the activity of coenzyme F430 . The methanogenic coenzyme F430 was demonstrated to significantly reduce the energy barrier to dechlorination …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous studies found that PCB71 and PCB149 could be extensively dechlorinated in Hudson and Grasse River sediments with similar levels of Dehalococcoides but with a more prevalent methane production. , It was reported that methanogens might assist dechlorination through the activity of coenzyme F430 . The methanogenic coenzyme F430 was demonstrated to significantly reduce the energy barrier to dechlorination …”
Section: Discussionmentioning
confidence: 98%
“…66 The methanogenic coenzyme F430 was demonstrated to significantly reduce the energy barrier to dechlorination. 67 The response of microbes to PCB dechlorination was further demonstrated through the analysis of the microbial community composition. PCBs remarkedly decreased the microbial community richness and evenness and drove the shifts of the microbial community composition.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Quantitative phenotyping tools also allow researchers to delve deeper into the mechanisms behind the formation of certain traits in tomato fruit at the genetic level ( Marefatzadeh-Khameneh et al, 2021 ). Research on the association network analysis between tomato fruit color and metabolic pathways would possibly be accelerated further as well ( Hu et al, 2020 ; Yuan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the changes in taxonomic composition during enrichment (Figure a), fermentative (e.g., Petrimonas, Sedimentibacter, and Anaerolineaceae), methanogenic (e.g., Methanosarcina and Methanofollis), and sulfate-reducing microorganisms (e.g., Desulfomicrobium and Desulfobulbus), together with Dehalococcoides, were present in the enrichments and original sediment microcosms alike. Some of these none-OHRB microbial populations may contribute to enhancing robustness of dehalogenation, for example, by supplying beneficial nutrients and maintaining anerobic conditions …”
Section: Resultsmentioning
confidence: 99%
“…Some of these none-OHRB microbial populations may contribute to enhancing robustness of dehalogenation, for example, by supplying beneficial nutrients and maintaining anerobic conditions. 47 Identification of Known Obligate OHRB and RDase Genes. To further quantify the growth of obligate OHRB and identify putative RDase genes responsible for the observed dehalogenation in marine enrichment cultures E, F, and P, qPCR was performed.…”
Section: ■ Resultsmentioning
confidence: 99%